Jigsaw Type of Cooperative Learning Model to Increase Learning Outcome in Learning Principal Science: Composition of Human and Animal Respiratory Organs - Walmiati, Walmiati (International Journal of Management and Education in Human Development, 2021)
This research is motivated by the low value of science subjects at SDN 100 Kendari which is caused by the science learning process that has been carried out so far still applying traditional learning patterns. Based on the above background, the following problems are formulated: (1) How is the application of jigsaw type cooperative learning in increasing mastery of concepts on the subject of Human and animal respiratory organ structure for fifth grade students at SDN 100 Kendari and (2) Can the application of the jigsaw type cooperative learning model improve science learning outcomes for fifth graders at SDN 100 Kendari? This study aims to: (1) Increased student reasoning skills class V SDN 100 Kendari material Milk nan respiratory organs of humans and animals use jigsaw type cooperative learning model; (2) Improved learning outcomes of fifth graders at SDN 100 Kendari on the subject of human and animal respiratory organ structure using Jigsaw cooperative learning ; and (3) Increasing the ability of teachers to guide students by applying the jigsaw type cooperative learning model in studying the composition of human and animal respiratory organs at SDN 100 Kendari. This type of research is classroom action research, as a research procedure that produces descriptive data in the form of written or spoken words from observable evaluation results. The population of this study was the fifth-grade students of SDN 100 Kendari, totaling 28 people. The results obtained indicate that the application of the jigsaw type cooperative learning model can improve the learning outcomes of fifth grade students at SDN 100 Kendari for science subjects. The achievement of performance indicators has been achieved where the classical average in the first cycle reaches 73.23 and the percentage of classical completeness is 77. .93, while in the second cycle there was an increase where the classical average had reached 78.57 and the classical completeness percentage had reached 82.14. Based on this, the performance indicators in this study are the classical average of 75 and the classical percentage of success is 80%.